2021
DOI: 10.1111/pedi.13206
|View full text |Cite
|
Sign up to set email alerts
|

Development of type 2 diabetes in adolescent girls with polycystic ovary syndrome and obesity

Abstract: Objective: Adult women with polycystic ovary syndrome (PCOS) and obesity have an 8-fold increased risk of developing type 2 diabetes (T2D). Our goal was to determine the incidence and risk factors for T2D in adolescents with PCOS and obesity.Research design and methods: Retrospective chart review of girls aged 11-21 years with confirmed PCOS (oligomenorrhea and hyperandrogenism) diagnosis between July 2013 and Aug 2018 and at least one follow-up visit and BMI >85%ile. T2D incidence, defined with an HbA1c ≥6.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…There is evidence that dysglycemia and HS are present early in PCOS, especially in girls with obesity. For instance, we found that 32% of adolescents with PCOS and obesity showed evidence of dysglycemia (22). Additionally, the incidence rate of developing T2D was up to 22‐fold higher in girls with PCOS; those at highest risk of developing T2D had evidence of prediabetes and HS at the time of PCOS diagnosis (22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is evidence that dysglycemia and HS are present early in PCOS, especially in girls with obesity. For instance, we found that 32% of adolescents with PCOS and obesity showed evidence of dysglycemia (22). Additionally, the incidence rate of developing T2D was up to 22‐fold higher in girls with PCOS; those at highest risk of developing T2D had evidence of prediabetes and HS at the time of PCOS diagnosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of association among this cohort of relatively healthy girls with obesity may reflect an early disease state and it is also similar to what has previously been shown in youth (8,10). Whereas adolescents with PCOS have a 22‐fold increased risk of developing T2D, our analysis only included girls without diabetes (22). A cohort including girls with worse pancreatic dysfunction and dysglycemia may demonstrate a stronger relationship between androgens and PFF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( Teede et al, 2018 ) The diagnosis of POCS in adolescents is based on the presence of menstrual irregularity for gynecological age and clinical (i.e., hirsutism or severe acne) or biochemical hyperandrogenism ( Teede et al, 2018 ; Peña et al, 2020 ) Apart from the reproductive dysfunction of PCOS, several metabolic comorbidities are thought to either exacerbate or drive the development of PCOS, including obesity, insulin resistance, and non-alcoholic fatty liver disease (NAFLD), albeit mechanisms have not been clearly delineated. Metabolic co-morbidities develop early; adolescents with PCOS and obesity have an 18-fold higher incidence of developing type 2 diabetes ( Hudnut-Beumler et al, 2021 ), a prevalence of NAFLD of 40–60%% ( Carreau et al, 2019 ; Andrisse et al, 2021 ). Understanding the unique etiologies of PCOS which manifest in adolescence and their respective biomarkers are needed for early, effective interventions to prevent or mitigate such deleterious health outcomes.…”
Section: Introductionmentioning
confidence: 99%